The comparative study of self-esteem and achievement motivation between vocational training school and high school. - Sarndhong, K.; Pittarattanasatian, N. (Chulalongkorn Medical Journal, 2023)
Background : Self-esteem and achievement motivation are related to development of adolescence. The more self-esteem and achievement motivation one has, the more one has better quality of life and mental health. Objective : To study of comparison as well as relative factors of self-esteem and achievement motivation of students in vocational training school and high school. Design : A cross-sectional descriptive design. Setting : Santirat Institute of Business Administration and Horwang School. Materials and Methods : In total, 120 students of avocational training school and high school who aged beween16 to 18 years old in academic year 2014 were recruited as subjects by simple random sampling methods. Data collected included: personal information, selfesteem questionnaires developed by Coopers Smith and achievement motivation questionnaires developed by McClelland. Data analysis was done using Independent t-test One-way ANOVA, Least Significant Difference (LSD) and Pearson Correlation. Result : From this study, the self-esteem of students in the vocational training school is significantly more higher than those in the high school with statistical difference at p <0.05. Furthermore, gender difference of a students in the high school is significantly related to levels of self-esteem with statistical difference at p <0.05. The achievement motivation mean of students in the vocational training school which at high level is similar to that of those in the high school ( = 58.12 and 57.33 respectively). Careers of the parents of the students in the vocational training school are significantly related to the levels of achievement motivation with statistical difference at p <0.05. Conclusion : In this study, self-esteem of students in vocational training school is higher than a those in the high school as well as gender difference of students in the high school is related to the self-esteem levels. Furthermore, their achievement motivation is no difference and careers of the parents of students in the vocational training school are related to their achievement motivation. The finding of the relative factors and the other sources will help related organizations regarding adolescence to understand them better and to apply for their development to be a better quality person in the future.